Gonadotropin-dependent pubertal disorders are common in patients with virilizing adrenocortical tumors in childhood. Issue 5 (May 2019) - Stecchini, Monica F; Braid, Zilda; More, Candy B; Aragon, Davi C; Castro, Margaret; Moreira, Ayrton C; Antonini, Sonir R
Abstract : Objective: To investigate the impact of early exposure to androgen excess on gonadotropin-dependent puberty (GDP) and final height (FH) of patients with androgen-secreting adrenocortical tumors (ACT) in childhood. Methods: Retrospective cohort study. Occurrence of GDP and achievement of FH were evaluated. Central precocious puberty (CPP) and early fast puberty (EFP) were considered pubertal disorders. Patients with normal puberty and pubertal disorders were compared. Results: The study included 63 patients (44F), followed in a single institution from 1975 until 2017. At diagnosis of ACT, median age was 25.8 months; duration of signs, 6 months; stature SDS, 0.5 (−3.6 to 3.9) and bone age advancement, 14.7 months (−27.9 to 85.4). To date, 37 patients developed GDP: 26 had normal puberty; one, precocious thelarche; seven, CPP and three, EFP. GnRHa effectively treated CPP/EFP. Tall stature and older age at diagnosis of ACT were associated with risk of CPP alone (RR 4.17 (95% CI 1.17–14.80)) and CPP/EFP (RR 3.0 (95% CI 1.04–8.65)). Recurrence/metastasis during follow-up were associated with risk of CPP alone (RR 4.17 (95% CI 1.17–14.80)) and CPP/EFP (RR 3.0 (95% CI 1.12–8.02)). Among the 19 patients that reached FH, stature SDS dropped from 1.4 to −0.02 since diagnosis of ACT ( P  = 0.01). Seventeen achieved normal FH. There was no difference in FH SDS between patients with normal puberty and pubertal disorders ( P  = 0.75). Conclusions: Gonadotropin-dependent pubertal disorders are common in patients with androgen-secreting ACT in childhood. FH is usually not impaired. The study reinforces the importance of close follow-up after surgery to identify and treat consequences of early exposure to androgen excess.